Neocolonialism in Black Panther “Wakanda forever” Movie - Kusen, Felicia Jessica; Saputra, Felicia Celine; Tambunan, Aubrey Jemima; Silaen, Gwyneth Lillian; Patricia, Catherine (Jurnal Pendidikan Makarios, 2023)
This study aims to show Neocolonialism in the movie "Black Panther: Wakanda Forever," employing the analytical framework of Marxism by Karl Marx and complemented by Foucault's theory of Power. The analysis unveils the disapproval of neocolonialism from Karl Marx's perspective through an in-depth exploration of the movie. The visual composition of the cinematography is conveyed along with the analysis of the movie. Embracing the Marxist approach, this study investigates the neocolonialism caused by external powers’ interest in the movie that has divided people even between social classes: Underwater Kingdom vs Wakanda. Three primary outcomes of neocolonialism emerge: 1) Resource Exploitation and Expansion (Namor): Namor, as the king of Sea peoples, represents the pursuit of expanding a powerful and resource-rich kingdom's interests. His actions could mirror neocolonial tendencies by seeking to control and exploit resources beyond his own nation's borders by any means: coercive, persuasive, or by force, mirroring neocolonizers. 2) Technological Protection and Resistance (Shuri): Shuri embodies the spirit of resistance against neocolonialism through her efforts to safeguard Wakanda's advanced technology. Her actions reflect a determination to prevent the appropriation of Wakanda's innovations by external forces, thereby preserving the nation's sovereignty and preventing technological exploitation. 3) Liberation and Ideological Influence (Erik Killmonger): While not physically present, Killmonger's legacy influences the resistance perspective. His radical ideals of liberating oppressed communities using Wakanda's resources align with resistance's goals, highlighting the potential outcome of neocolonialism where powerful nations may manipulate resources to advance their ideological interests.